Comparative Antimicrobial Profiling of Synedrella nodiflora L. and Spilanthes calva DC. Through Integrated In Vitro, In Silico and Phytochemical Screening Approaches - Islam, Md Anisul; Chowdhury, Sakib; Suma, Khurshida Jahan; Mohammad, Mahathir; Hossain, Md Aslam; Mamun, Md Jahirul Islam; Moon, Nusrat Jahan; Alam, Safaet (Bangladesh Pharmaceutical Journal, 2026)
The Asteraceae family includes numerous medicinal plants known for their broad-spectrum therapeutic properties, particularly antimicrobial activity. This study evaluates the phytochemical profiles and antimicrobial activity of methanol extracts from leaves of Synedrella nodiflora L. (MESN) and Spilanthes calva DC. (MESC), two Bangladeshi Asteraceae species, using in vitro disc diffusion assays and in silico docking, PASS prediction, and ADMET analysis. Phytochemical screening revealed glycosides, gums, flavonoids, and tannins in both (MESN also contained steroids); no alkaloids or reducing sugars were detected. Antimicrobial activity was evaluated via the disc diffusion method using 50 µg/disc extract concentrations. MESN demonstrated moderate antibacterial activity against Staphylococcus aureus (14.0 mm) and notable activity against Shigella dysenteriae (21.5 mm) and Shigella sonnei (23.5 mm). MESC exhibited broader and stronger antibacterial effects, with inhibition zones ranging from 13 mm to 30 mm across tested strains. In antifungal assays against seven pathogenic species, MESN showed significant activity against Blastomyces dermatitidis (22.0 mm) and Microsporum spp. (23.0 mm), while MESC displayed considerable inhibition against most fungi, except Trichophyton spp., with zones ranging from 7.5 mm to 24.0 mm. To complement in vitro findings, molecular docking, PASS prediction and ADMET SAR analyses were conducted on commonly identified phytochemicals from these two plants to evaluate their binding affinities, predicted biological activities and pharmacokinetic properties. These in silico analyses confirmed drug-likeness and binding affinities, supporting therapeutic potential against resistant pathogens. In conclusion, the study highlights the therapeutic promise of S. nodiflora and S. calva as sources of natural antibacterial and antifungal agents. The integration of phytochemical analysis, microbiological assays, and computational modeling underscores their potential for future drug development. Bangladesh Pharmaceutical Journal 29(1): 119-133, 2026 (January)